Dosis de ácido humico granulado de leonardita en el cultivo de col china (Brassica Pekinensis) variedad Kiboho 90 f-1, sector Quillo Allpa – distrito y provincia de Lamas - Lopez Vasquez, Tiberio (2013)
The paper titled "Dose leonardite humic acid granules in growing Chinese cabbage (Brassica pekinensis) kiboho range 90 f-1, Sector allpa sleeve - district and province of Lamas", The objectives were: evaluate three doses of leonardite humic acid granules in the cultivation of Chinese cabbage (Brassica pekinensis) Variety Kiboho 90 F-1, determine the dose of leonardite humic acid granules with better results in the production of Chinese cabbage (Brassica pekinensis) Variety Kiboho 90 F-1 and make economic analysis of the treatments studied. For the implementation of this experiment we used the statistical design of randomized complete block (RCBD) with four blocks and four treatments. The treatments were: T1: Application of 100 kg ha-1 (6 grams x experimental unit), T2 They applied 200 kg ha-1 (12 grams x experimental unit), T3 Application of 300 kg ha-1 (18 grams x experimental unit) and T0 (No Application). The main conclusions were that the T3 (300 kg ha-1), T2 (200 kg ha-1) and T1 (100 kg ha-1) with averages of 3.29 kg, 3.25 kg and 3.18 kg of inflorescence respectively were statistically equal, surpassing the average achieved by the T0 (control) who showed the lowest average at 2.87 kg inflorescence. The T2 (200 kg ha-1), T3 (300 kg ha-1) with an average of 1028.84 and 1026.63 Tn.ha-1-1 performance Tn.ha were statistically equal to each other and beating treatments T1 (100 kg ha-1) and T0 (control) who achieved averages of 978.77 and 872.1 Tn.ha Tn.ha-1-1 respectively. All treatments yielded indices Cost / Benefit positive, with values of 43.37, 43.30, 42.85 and 42.22 for T0, T1, T2 and T3 respectively